Assessing Habitat Suitability for Juvenile Atlantic Salmon in Relation to In‐Stream Restoration and Discharge Variability. Issue 3 (27th September 2012) - Koljonen, Saija; Huusko, Ari; Mäki‐Petäys, Aki; Louhi, Pauliina; Muotka, Timo
Abstract In‐stream restoration often aims at increasing the availability of the stream habitat suitable for salmonid fishes, thus creating potential for increased fish abundance. We assessed the success of in‐stream restoration of River Kiiminkijoki, northern Finland, by combining River2D habitat hydraulic modeling and fish density monitoring at the same sites, with data from multiple restored and reference reaches for 3 years both before and after restoration. We modeled the effects of restoration on the area suitable (weighted usable area, WUA) for juvenile Atlantic salmon from post‐hatching to age‐1 fish. Wetted width in the restored reaches increased by 8.1% on average compared with only −0.2% change in the reference reaches. Habitat time series across 10 years showed significant increases in the amount of suitable habitat under summer conditions for both age‐0 and age‐1 salmon. However, improvement of overwintering habitats was marginal or nonexistent. Densities of age‐1 salmon showed no response to restoration. Low river discharge during the winter was correlated with low salmon densities the following summer. It thus appears that variability in wintertime discharge, and associated high interannual variation of WUA values, overrode the almost 20% increase in average post‐ versus pre‐restoration summertime WUA. Our study shows that the combination of hydraulic modeling and biological monitoring is a promising approach to stream restoration assessment.